Lamellarity of ultrasound assisted formations of dipalmitoyl-lecithin vesicles - Attila Bóta; Heinz Amenitsch; András Wacha (Ultrasonics Sonochemistry, 2025)
Formation of unilamellae of fully hydrated dipalmitoylphosphatidylcholine (DPPC) was induced by a horn sonicator from multilamellar vesicles and followed by time-resolved synchrotron small angle X-ray scattering and direct visual morphological investigations by the means of transmission electron-microscopy combined with freeze-fracture. Without incubation the ultrasonication causes continuous increasing in temperature and transformation from the gel to rippled gel structures, then reaching the main transition, the formfactor of unilamellar structure appeared. The ultrasonication resulted in different layer formations at the characteristic temperatures of the gel (20 °C), rippled gel (38 °C), and liquid crystalline (45 °C) phases of the system. At 20 °C irregular stacks of multi and oligolamellar lamellae were shaped even after three hours of ultrasonication. At 38 and 45 °C the ultrasound induced dominantly unilamellar vesicles (ULVs) in a short time (10 and 3 – 5 min, respectively, under typical ultrasound treatments in the general laboratory practice). After the end of the ultrasonication, irregular layer formations with defects structures increased when the temperature of sonication was above the chain melting temperature of the hydrated DPPC system, underlining the importance of optimized sonication processes.